Exploring the Cadmium Tolerance and Removal Capability of a Filamentous Fungus Fusarium solani. Issue 9 (21st October 2019) - Kumar, Vinay; Singh, Saumya; Singh, Garima; Dwivedi, S. K.
Abstract: Cadmium is one of the most toxic contaminant causing many problems to human health and the environment. These days the world is moving toward ecofriendly and efficient techniques to remove the pollutant from the wastewater. The present study aims to investigate the tolerance of Fusarium solani toward cadmium (Cd), nickel (Ni), and lead (Pb). Maximum tolerance was observed with Cd. Cadmium removal ability of F. solani was examined from contaminated PDB medium. pH, initial concentration and time optimization for maximum removal of Cd by F. solani was also studied. The maximum removal (92.4%) was recorded at initial concentration of 50 mg/L after 144 h of incubation. Cadmium exposure increased the level of glutathione (GSH) and oxidized glutathione (GSSG) contents and the activity of catalase (CAT) in F. solani . Fourier-transform infrared spectroscopy (FTIR) analysis indicated the involvement of the different surface functional group in biosorption of Cd while Scanning Electron Microscopy coupled with Energy Dispersive Spectroscopy (SEM-EDS) analysis revealed the presence of Cd on the surface of fungal cell. The changes observed in compositions of S, P, and Cd using EDS analysis on biomass surface indicated the precipitation of Cd as CdS and Cd3 (PO4 )2 . The XRD analysis revealed the presence of Cd3 (PO4 )2 on mycelia surface of F. solani .